Biotransformation of sesquiterpenoids: a recent insight - Aminudin, Nurul Iman; Ridzuan, Munirah; Darnis, Deny Susanti; Zainal Abidin, Zaima Azira (Taylor & Francis, 2022)
Sesquiterpenoids have been identified as natural compounds showing remarkable biological activities found in medicinal plants. There is great interest in developing methods to obtain sesquiterpenoids derivatives and biotransformation is one of the alternative methods for structural modification of complex sesquiterpenes structures. Biotransformation is a great drug design tool offering high selectivity and green method. The present review describes a comprehensive summary of biotransformation products of sesquiterpenoids and its structural modification utilizing a variety of biocatalysts including microorganisms, plant tissue culture and enzymes. This review covers recent literatures from 2007 until 2020 and highlights the experimental conditions for each biotransformation process.